The association of hydrogen with sulfur on Mars across latitudes, longitudes, and compositional extremes. Issue 7 (22nd July 2016) - Karunatillake, Suniti; Wray, James J.; Gasnault, Olivier; McLennan, Scott M.; Deanne Rogers, A.; Squyres, Steven W.; Boynton, William V.; Skok, J. R.; Button, Nicole E.; Ojha, Lujendra
Abstract: Midlatitudinal hydrated sulfates on Mars may influence brine pH, atmospheric humidity, and collectively water activity. These factors affect the habitability of the planetary subsurface and the preservation of relict biomolecules. Regolith at grain sizes smaller than gravel, constituting the bulk of the Martian subsurface at regional scales, may be a primary repository of chemical alteration, mechanical alteration, and biosignatures. The Mars Odyssey Gamma Ray Spectrometer with hundreds of kilometers of lateral resolution and compositional sensitivity to decimeter depth provides unique insight into this component of the regolith, which we call soil. Advancing the globally compelling association between H2 O and S established by our previous work, we characterize latitudinal variations in the association between H and S, as well as in the hydration state of soil. Represented by H2 O:S molar ratios, the hydration state of candidate sulfates increases with latitude in the northern hemisphere. In contrast, hydration states generally decrease with latitude in the south. Furthermore, we observe that H2 O concentration may affect the degree of sulfate hydration more than S concentration. Limited H2 O availability in soil‐atmosphere exchange and in subsurface recharge could explain such control exerted by H2 O on salt hydration. Differences in soil thickness, ground ice table depths, atmospheric circulation, and insolation may contribute to hemispheric differences in the progression of hydration with latitude. Our observations support chemical association of H2 O with S in the southern hemisphere as suggested by Karunatillake et al. (2014), including the possibility of Fe sulfates as a key mineral group. Key Points: Unique Mars Odyssey GRS insight into bulk soil hydration at decimeter depth Limited H2 O in soil‐atmosphere exchange and recharge may control salt hydration H2 O and S chemically associated in the South, with Fe sulfates as key minerals